CONCEPTUAL MODELING OF A SITUATIONALLY AWARE VIDEO SURVEILLANCE SYSTEM BASED ON INTERNET OF THINGS TECHNOLOGY - KUNANETS, NATALIIA; ZHOVNIR, YURIY; VEREMEENKO, ANDRII; PUSHCHAK, SEMEN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is dedicated to the conceptual modeling of a situationally aware video surveillance system based on Internet of Things (IoT) technology. A situationally aware approach is proposed, integrating intelligent devices, machine learning algorithms, and analytical tools to enable effective monitoring, threat detection, and automated incident response. The focus is on a conceptual model using UML diagrams, which are employed to formalize the structure, functionality, and interactions of system components. The article examines the key components of the system: sensors, cameras, situational analysis software, data storage and visualization systems, as well as modules for event forecasting and risk management. The Use Case Diagram describes the main usage scenarios, including real-time monitoring, archival data analysis, and anomaly response. The Sequence Diagram demonstrates the interaction between system components in real time, for example, during motion detection or a threat event. Special attention is given to the Class Diagram, which represents the software structure, including classes for data processing, device management, and analytical and visualization modules. The Component Diagram details the system architecture, emphasizing the integration between IoT devices, server components, and cloud services. The Deployment Diagram models the physical infrastructure of the system, covering cameras, sensors, network devices, servers, and mobile applications. The proposed approach ensures scalability, adaptability, and high efficiency of the video surveillance system, enabling real-time threat detection, risk prediction, and prompt response. The use of conceptual modeling facilitates the creation of a system that meets modern security requirements, integrates with other information systems, and considers the energy consumption constraints of IoT devices. The article highlights the importance of UML diagrams in formalizing complex architectural solutions and planning their implementation.